SOCIOECONOMIC STATUS, PARENTAL INVOLVEMENT IN LEARNING AND STUDENT’ MATHEMATICS ACHIEVEMENT IN INDONESIAN SENIOR HIGH SCHOOL - Kusaeri, Kusaeri; Aditomo, Anindito; Ridho, Ali; Fuad, Ah. Zakki (LPMPP Universitas Negeri Yogyakarta, 2018)
Abstract: The objectives of the research are to examine: (1) the relationship between parents’ education level as an indicator of socioeconomic status (SES) with students’ mathematics achievement, and (2) the interaction between parents’ education level and the intensity of parental involvement in predicting students’ mathematics achievement. The sample (N=2,867) was selected through stratified random sampling of Indonesian high school National Examination (NE) test takers in 2016. The sampling was based on careful consideration of the representativeness and the distribution of provinces, gender, type of school (general-vocational), and school status (public-private). Data was analyzed using parallel multiple mediator analyses. The findings highlight that: (1) compared to fathers, mothers’ education level had a stronger contribution to students’ achievement in mathematics, and (2) mothers’ involvement mediated the relationship between mothers’ level of education and students’ mathematics achievement. However, more intensive parental involvement was associated with lower mathematics achievement. Keywords: SES, mathematics, parents’ education levels, involvement STATUS SOSIAL EKONOMI, KETERLIBATAN ORANGTUA DALAM BELAJAR DAN HASIL BELAJAR MATEMATIKA SISWA SMA DI INDONESIA Abstrak: Penelitian ini bertujuan untuk menguji: (1) kaitan antara tingkat pendidikan orangtua sebagai indikator status sosial ekonomi (SSE) dengan hasil belajar matematika siswa, dan (2) interaksi antara tingkat pendidikan orangtua dengan intensitas keterlibatan orangtua dalam memprediksi hasil belajar matematika anak-anaknya. Sampel penelitian ini (N=2,867) dipilih secara stratified random sampling dari peserta Ujian Nasional di Indonesia tahun 2016 jenjang SMA. Pengambilan sampel didasarkan pada keterwakilan dan sebaran provinsi, jenis kelamin, jenis sekolah (SMA/MA atau SMK) dan status sekolah (negeri-swasta). Data dianalisis dengan menggunakan analisis parallel multiple mediator. Hasil penelitian menunjukkan: (1) pendidikan ibu memiliki peran sangat penting karena sangat berkonstribusi dalam menunjang hasil belajar matematika anaknya dibandingkan pendidikan ayah, dan (2) keterlibatan ibu dalam belajar anak yang dimediasi tingkat pendidikannya berpengaruh terhadap hasil belajar matematika anaknya. Namun demikian, keterlibatan orangtua yang terlalu intens dalam kegiatan belajar anak justru berdampak kurang baik terhadap hasil belajar matematika anaknya. Kata Kunci: SSE, matematika, tingkat pendidikan orangtua, keterlibatan